Interactive Learning Media Based on Website in Vocational School - Ferdiansyah Ferdiansyah; Dedy Irfan (STAI Hubbulwathan Duri, 2021)
This study aims to develop website-based interactive learning media in the vocational school. This research is a type of R and D research using the Four-D model, namely: define, design, develop, and dissemination. The data used are primary, namely data directly from the source, including experts as validators, educators, and students. Data collection was carried out through tests, questionnaires, and interviews. The data analysis used was referential statistical analysis to test the validity of the data, practicality, and effectiveness. This study indicates that this website-based interactive learning media is valid, practical, and effectively used as a learning media. Based on the validity, practicality, and effectiveness of test results, website-based interactive learning media can be developed, which can be a renewal in overcoming learning difficulties of students of SMKN 2 Padang on computer and basic network subjects. Therefore, it can be concluded that the learning process and outcomes can be improved through website-based interactive learning media.